Impact of the use of hydroxyethyl starch in granulocyte apheresis using Spectra Optia. Issue 5 (6th June 2021) - Yoshihara, Satoshi; Ikemoto, Junko; Onomoto, Hitomi; Sugiyama, Hiroki; Okuda, Noriko; Fukunaga, Keiko; Yoshihara, Kyoko; Kaida, Katsuji; Ikegame, Kazuhiro; Tamaki, Hiroya; Okada, Masaya; Osugi, Yuko; et al.
Abstract: Objectives: To determine the impact of the use of hydroxyethyl starch (HES) in granulocyte apheresis using Spectra Optia. Background: Granulocyte transfusion (GT) is a therapeutic option for neutropenic patients with severe bacterial or fungal infections. Recent studies in emergency medicine have shown the potential risk of using HES, which is routinely used in granulocyte apheresis to increase yield by sedimenting red blood cells. We hypothesized that the use of a newer device (Spectra Optia) would spare the need for HES. Methods: We retrospectively compared granulocyte apheresis with HES (HES group, n = 89) and without HES (non‐HES group, n = 36) using Spectra Optia. Results: The granulocyte yield was significantly higher in the HES group (7.3 × 10 10 vs. 2.0 × 10, p < 0.01) and was attributed to the difference in collection efficiency (36% vs. 7.7%, p < 0.01). The absolute neutrophil count on the following morning of GT was significantly higher in the HES group than in the non‐HES group (2460/μl vs. 505/μl, p < 0.01). There were no significant differences in the occurrence of adverse events between the HES and non‐HES groups. The renal function was unchanged in both groups after apheresis. Conclusions: We demonstrated that the advantage of using HES remained unchanged in granulocyte apheresis using Spectra Optia.